2016
DOI: 10.1155/2016/4021928
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Clues of Pulmonary Alveolar Proteinosis: A Report of 11 Cases and Literature Review

Abstract: Pulmonary alveolar proteinosis (PAP) is a rare interstitial lung disease characterized by the abnormal alveolar accumulation of surfactant components. The diagnosis of PAP can be easily missed since it is rare and lacks specific clinical symptoms. It is of great importance to have a better understanding of the crucial clue to clinically diagnose PAP and take PAP into consideration in the differential diagnosis of interstitial pulmonary diseases or other diseases with similar manifestations. Here, we analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Lung function findings from this study agree with published observations 4 , 14 , 22 , 25 27 . In patients with aPAP, DL CO is frequently reduced, whereas FVC and FEV 1 are generally within normal limits (although some patients with aPAP show decreased FVC) 26 , 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Lung function findings from this study agree with published observations 4 , 14 , 22 , 25 27 . In patients with aPAP, DL CO is frequently reduced, whereas FVC and FEV 1 are generally within normal limits (although some patients with aPAP show decreased FVC) 26 , 28 .…”
Section: Discussionsupporting
confidence: 92%
“…In a study by Mo et al in which they examined 11 PAP patients, a total of 8 patients had BAL procedure done. Their results showed that patients with a large alveolar lavage volume and/or bilateral lavage had a greater improvement in PaO2 than those who had less volume and/or unilateral lavage, subsequently leading to the conclusion that high-volume lavage is more effective in the treatment of PAP [10].…”
Section: Resultsmentioning
confidence: 99%
“…It is about two‐fold more common in male than in female, and is more common in smokers or those with a positive history of causative exposure. The onset is usually insidious, with such non‐specific symptoms as dyspnoea, cough, fatigue, and occasionally fever . Pulmonary function tests almost consistently reveal a reduction in the DLco indicating the presence of ventilation‐perfusion mismatch, with or without a restrictive‐type ventilatory deficit .…”
Section: Discussionmentioning
confidence: 99%